If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -10x = 4 + x Solving 3 + -10x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + -10x + -1x = 4 + x + -1x Combine like terms: -10x + -1x = -11x 3 + -11x = 4 + x + -1x Combine like terms: x + -1x = 0 3 + -11x = 4 + 0 3 + -11x = 4 Add '-3' to each side of the equation. 3 + -3 + -11x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + -11x = 4 + -3 -11x = 4 + -3 Combine like terms: 4 + -3 = 1 -11x = 1 Divide each side by '-11'. x = -0.09090909091 Simplifying x = -0.09090909091
| 3b=11/2 | | =3x^2-10x | | 6(2-x/6=1 | | (2x-15)+(3x+10)+2x=180 | | 3(4-1)-7x=17 | | 6(7x+7)=-6(x+1) | | 4x-5[4(x+3)-(x-2)]-5= | | (r-2)(r+10)=-9 | | X-5/14=4/7 | | 1-(2)/(5)y=4x-3 | | (4x-28)+(9x-17)+30=180 | | (7+7d)+(-5+9m)= | | 2.2x=12.76 | | 6.3k-1.4+3.5=52.5 | | -(2k+4)-4(k+4)=4k-8k | | 14x^2-46x+1=0 | | f(-1)=8x^5+2x | | 2s-1s= | | 3(1+6p)=-5p+3 | | F(x)=4x^2+2x+6 | | (3z-2)/-56 | | w^4=144 | | 3.4-4x= | | x-0.02x=510 | | 9(2h+3)-4(4h-6)= | | x+y+115=180 | | 32k-4=5k-32 | | (7+6x)+(-5+7d)= | | 3x-8y=34 | | 21*2x+8=27x | | =15x^2-4 | | 13x+11=20x-38 |